A comparative study of dispersed and grafted nanofluids of graphene nanoplatelets with natural polymer in high salinity brine for enhanced oil recovery - Hamdi, S.S. (Elsevier B.V., 2022)
Polymer flooding as one of conventional chemical enhanced oil recovery (C-EOR) techniques has high potential for declining the mobility ratio and improving oil recovery. The degradation, toxicity, and cost are inherent restrictions in polymer performance at high salinity and high temperature. Recently, incorporation of nanoparticles with a polymer to produce polymeric nanofluids has acquired a great interest as the newest trends of development in nanotechnology for EOR processes. In this study, a comparative evaluation of functionalized graphene nanoplatelets (GNPs) were prepared by two different methods of mixing and grafting with natural Polymer of Gum Arabic (GA). These methods aimed to improve the dispersion stability of the nano-additives in high salinity brines and high temperature conditions for promising alternative C-EOR agent. The physiochemical properties of the functionalized GNPs were characterized by Fourier transform-infrared spectroscopy, Raman spectroscopy, and transmission electron microscope. The zeta potential, dynamic light scattering, and optical absorbance were employed to evaluate the effective dispersion stability of the prepared nanofluids in high salinity concentration 3 wt and temperature at 90 Â°C. The laboratory results indicated that the dispersion and rheological properties revealed a stable dispersibility of Polymer grafted GNPs (PG-GNPs) in high salinity brine even with high temperatures compared to Polymer dispersed GNPs (PD-GNPs) at low concentration 0.05 mg/mL. However, it was observed that the nature of functionalized GNPs with GA has a significant role in increment the capillary number via reducing the value of interfacial tension (IFT) and modification the wettability of pores surface inside the heterogenous micromodel. The core flooding findings of nanofluids injection in the mid permeable sandstone porous media showed that oil recovery enhanced by around 17 and 5 at 0.05 mg/mL of PG-GNPs and PD-GNPs, over the conventional water flooding. Consequently, the overall results of PG-GNPs exhibited better performance compared to PD-GNPs due to successful GNPs layers exfoliation which led to stable dispersion with the same concentration of 0.05 mg/mL at reservoir conditions. Â© 2021 Elsevier B.V.